THE EDUCATION PILLAR IN MALAYSIA MADANI: FOSTERING STUDENT DEVELOPMENT FOR A DEVELOPED MALAYSIA - Nor Azira Mohd. Radzi; Majdah Chulan; Azhar Abdul Rahman, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The study explores strategies to strengthen holistic education by balancing academic and non-academic development, emphasizing life skills, critical thinking, emotional intelligence, and employability competencies. Equity in education is addressed through targeted interventions such as scholarships, infrastructure improvements in rural schools, and inclusive learning environments that cater to diverse needs. Innovation and technology are examined as essential tools for preparing students for the digital economy, with recommendations for integrating digital literacy and coding into curricula while bridging the digital divide through infrastructure investments. Additionally, the paper highlights challenges related to teacher quality and professional development. It underscores the need for competitive salaries, career advancement opportunities, and ongoing training to equip educators with effective pedagogical strategies and technological proficiency. Parental and community involvement is also emphasized as a critical factor in student success, advocating for initiatives such as parent-teacher associations and community-based programs. By aligning Malaysia’s education system with the principles of Malaysia Madani—sustainability, prosperity, innovation, respect, trust, and compassion—this paper provides actionable recommendations for policymakers, educators, and stakeholders to address systemic inequities. These findings contribute to the discourse on educational reform in Malaysia while offering insights into fostering a more inclusive and innovative learning environment.